2018
DOI: 10.1038/s41598-018-26638-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of religion on hypertension in adult Buddhists and residents in China: A cross-sectional study

Abstract: Correlation between religion and hypertension is worth investigating since they both influence many people. Compared to studies which quantify religion with indicators representing only restricted dimensions of religion, researches assessing religion as an integral is preferable while lacking. Moreover, religious behaviors have great potential to be generalized if they are proved to be mediator through which religion exerts effect. However, relevant evidence is limited. Therefore, this cross-sectional study re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
3
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 40 publications
1
21
3
5
Order By: Relevance
“…We found that even though most respondents were associated with a religion, is unprotective from having high blood pressure, asthma, diabetes, and heart problem compared to those who had no religion. This is contrary to the ndings of Meng et al [46], who suggested that religion bene ts control and prevention of blood pressure in patients. The scenario is similar to other cardiovascular diseases and NCDs [45].…”
Section: Discussioncontrasting
confidence: 95%
“…We found that even though most respondents were associated with a religion, is unprotective from having high blood pressure, asthma, diabetes, and heart problem compared to those who had no religion. This is contrary to the ndings of Meng et al [46], who suggested that religion bene ts control and prevention of blood pressure in patients. The scenario is similar to other cardiovascular diseases and NCDs [45].…”
Section: Discussioncontrasting
confidence: 95%
“…From this perspective, our study fills in the gaps in the field by using the KAP survey developed by the World Hypertension League. The poor hypertension management ability of physicians, limited medical resources, together with the natural environmental characteristics, 15 contributed to the poor hypertension management quality as our previous study suggested in this high‐altitude region, which was mainly characterized by a high disease prevalence and a relatively low control rate 15 …”
Section: Discussionmentioning
confidence: 96%
“…The religious active adults tend to have lower blood pressure than those who are less active. This also applies to attendance of religious services and private religious activities (Meng, et al, 2018;Meng et al, 2019;Sorenson, 2011). Cross sectional analysis has revealed consistent differences in the measured systolic blood pressure between frequent and infrequent religious service attenders.…”
Section: Introductionmentioning
confidence: 82%
“…Cross sectional analysis has revealed consistent differences in the measured systolic blood pressure between frequent and infrequent religious service attenders. Lower blood pressure were observed among those who frequently prayed or studied the bible (Meng et al, 2018;Meng et al, 2019;Sorenson, 2011).…”
Section: Introductionmentioning
confidence: 97%